Kebijakan Fiskal dan Resistensi Sosial: Studi Kasus Protes Kenaikan Pajak di Kab. Pati Jawa Tengah 2025 - Teguh Abdul Aziz; Nida Arifah; Hizqiel Nadjib Yasin; Rapi Badrun Munawwar; Qiny Shonia Azzahra; Tuti Adi Tama (Economie: Jurnal Ilmu Ekonomi, 2026)
Fiscal policy serves as a crucial instrument for the government in managing economic conditions through state revenue and expenditure. However, the implementation of such policies often triggers public discontent, especially when it involves tax increases. This study explores the dynamics of social resistance to the tax hike policy enacted in Pati Regency, Central Java, in 2025. The research is grounded in the widespread protests by small and medium-sized enterprise (SME) actors who felt disadvantaged by the policy. A qualitative approach was employed, with data collected through in-depth interviews, direct field observation, and analysis of relevant documents. The findings reveal that social resistance was driven by inadequate public outreach, limited transparency in how tax funds were utilized, and perceptions of unfair tax burdens across business sectors. The study concludes that a more participatory, accountable, and locally adaptive fiscal policy is necessary to reduce the risk of social conflict and to ensure sustainable public revenue collection.